Laser-Induced Breakdown Spectroscopy in Vegetable Analysis: Contaminants and Nutrients - Anwar, Hafiza Ayesha; Rashid, Areesha; Muhammad, Rashid (The Nucleus, 2025)
Vegetables are rich in minerals, but pollutants and wastewater, which introduce heavy metals into the soil, heavily impact their cultivation. As an efficient and effective methodology, scientists prefer using Laser-Induced Breakdown Spectroscopy (LIBS) as a light-based technique to determine the elemental constituents of vegetables. It aids in safety and quality assurance by allowing them to image nutrients and hazardous metals, such as cadmium. This study explored the application of LIBS for detecting contaminants, such as Cd, and profiling essential nutrients in vegetables. Unlike conventional methods such as ICP-MS and AAS, LIBS offers fast, on-site, and multi-element analyses with minimal sample preparation. This review consolidates recent studies on carrots, potatoes, spinach, broccoli, and other leafy greens, emphasizing enhancements using nanoparticles and chemometric tools to improve sensitivity and accuracy. According to the results, LIBS has also been effectively employed to analyze the components of vegetables, enhancing the control and safety of food quality surveillance. The results also prove that LIBS can be a better method for monitoring food quality and safety. LIBS is more consumer-and environmentally friendly because it is portable, fast, and capable of simultaneously analyzing various components.